Temporal trends of enterococcal and vancomycin-resistant Enterococcus faecium bacteraemias in the northern Dutch-German cross-border region: a ten-year multicentre analysis - Cansu Çimen; Andreas Voss; Joseph Hellkamp; Axel Hamprecht; Matthijs Berends (Journal of Global Antimicrobial Resistance)
INTRODUCTION: Enterococcus species, particularly E. faecium and E. faecalis, are prominent causes of bacteraemia, posing significant clinical challenges due to antibiotic resistance. The incidence of enterococcal bacteraemia, especially vancomycin-resistant E. faecium (VREfm), has been rising in Europe. This study aims to map the trends in enterococcal bacteraemia and VREfm in the Northern Dutch-German cross-border region over a decade. METHODS: We conducted a retrospective cross-sectional study at the Dutch University Medical Center Groningen (UMCG) and German Klinikum Oldenburg (KOL) from January 1, 2013, to December 31, 2022. Data on enterococcal bacteraemia episodes, patient demographics, and antibiotic resistance were collected from blood cultures. RESULTS: A total of 1,822 episodes of enterococcal bacteraemia were identified, of which 733 at KOL and 1,089 at UMCG. VRE bacteraemia was significantly higher at KOL (67 cases) compared to UMCG (7 cases). Median ages for enterococcal bacteraemia were 67 years at KOL and 61 years at UMCG. The majority of cases were in males (68.2% at KOL, 63.4% at UMCG). Haematology/Oncology wards accounted for approximately 48% of enterococcal bacteraemia cases in both hospitals. DISCUSSION: Our findings reveal significant institutional and regional differences in the incidence and characteristics of enterococcal bacteraemia. These discrepancies highlight the need for localized surveillance for understanding the epidemiology of enterococcal bacteraemia, and tailored infection control strategies. The high burden of bacteraemia in Haematology/Oncology wards underscores the vulnerability of immunocompromised patients. Enhanced cross-border collaboration and data sharing are crucial for effective infection control in this interconnected region.